Charting the territory: symptoms and functional assessment in children with progressive, non-curable conditions. Issue 8 (15th May 2014) - Steele, Rose; Siden, Harold; Cadell, Susan; Davies, Betty; Andrews, Gail; Feichtinger, Leanne; Singh, Mina
Abstract : Background: Children with progressive, non-curable genetic, metabolic, or neurological conditions require specialised care to enhance their quality of life. Prevention and relief of physical symptoms for these children needs to begin at diagnosis, yet, little is known about their patterns of symptoms and functional abilities. Aim: To describe these children's symptoms, as well as how the children's condition affects them physically. Design: Cross-sectional, baseline results from an observational, longitudinal study, Charting the Territory, that followed 275 children and their families. Setting/participants: Seven tertiary care children's hospitals in Canada, 2 in the USA. Families were eligible based on the child's condition. A total of 275 children from 258 families participated. Results: The 3 most common symptoms in these children were pain, sleep problems, and feeding difficulties; on average, they had 3.2 symptoms of concern. There was a pattern of under-reporting of children's symptoms for clinicians compared with parents. Regardless of use of associated medications, pain, feeding and constipation symptoms were often frequent and distressing. Children with a G/J tube had a higher total number of symptoms, and respiratory problems, pain, feeding difficulties and constipation were more likely to occur. They also tended to have frequent and distressing symptoms, and to need extensive mobility modifications which, in turn, were associated with higher numbers of symptoms. Conclusions: These children experience multiple symptoms that have been previously documented individually, but not collectively. Effective interventions are needed to reduce their symptom burden. Future longitudinal analyses will examine which disease-modifying interventions improve, or do not improve, symptom burden.